2009
DOI: 10.1590/s0103-84782009000100001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between chemical properties of the soil and the occurrence of Bacillus thuringiensis

Abstract: The soil and other substrates such as mushroom compounds are the main sources of new Bacillus thuringiensis (Bt) isolates for Integrated Pest Management programs. This study describes the relationship between chemical properties of the soil (pH,OM INTRODUCTIONBacillus thuringiensis (Bt) is a widespread gram-positive spore-forming bacterium that produces toxic protein crystals named parasporal crystals. These inclusions are toxic to a wide variety of insects and many of them are commercially used against insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Bacillus thuringiensis (Bt) is often referred to as a soil microorganism simply due to the fact that it has been isolated from this environment for several years [ 34 , 35 ]. Other researchers believe that the Bt spores may only be stored in the soil since they hardly germinate there and need certain nutrients and pH levels for that to occur [ 36 , 37 ]. The native microbiota and soil characteristics, including pH, humidity, mineral and organic matter concentrations, have an immediate impact on the Bt viability, thereby affecting its growth, sporulation, germination, and protein synthesis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus thuringiensis (Bt) is often referred to as a soil microorganism simply due to the fact that it has been isolated from this environment for several years [ 34 , 35 ]. Other researchers believe that the Bt spores may only be stored in the soil since they hardly germinate there and need certain nutrients and pH levels for that to occur [ 36 , 37 ]. The native microbiota and soil characteristics, including pH, humidity, mineral and organic matter concentrations, have an immediate impact on the Bt viability, thereby affecting its growth, sporulation, germination, and protein synthesis [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The B. thuringiensis' isolates index variation from the soil samples may be related to the soil's chemical proprieties, such as type of nutrients, acidity and soil oxygenation, that can influence the B. thuringiensis prospection and the bacterium's toxins production (Yao et al, 2002;Polanczyk et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The B. thuringiensis var. israelensis (Bti) is the most powerful biological alternative for controlling some diseases' vectors around the world (Polanczyk et al, 2009;Ben-Dov, 2014). This species' larvicidal activity resides in toxic proteins encoded by the cry4Aa, cry4Ba, cry10Aa, cry11Aa, cyt1Aa, cyt1Ca and cyt2Ba genes (Berry et al, 2002;Costa et al, 2010;Ben-Dov, 2014), which are used in many commercial products indicated to the Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Others, however, consider the soil only as a storage milieu for Bt spores, as they barely germinate in these places, requiring specific nutrients and pH conditions for that [ 16 , 17 , 18 , 19 ]. The indigenous microbiota, as well as soil properties, such as pH, humidity, mineral and organic matter concentrations have a direct effect on Bt ’s survival, acting positively or negatively on germination, growth, sporulation, and production of proteins [ 18 , 20 , 21 , 22 , 23 ]. These conditions, on another hand, tend to have a much lesser effect on Bacillus cereus (a taxon very closely related to Bt ), which has shown the ability to multiply in non-sterilized soils, increasing its population up to 20% [ 17 ].…”
Section: Niches Occupied By Btmentioning
confidence: 99%
“…Moreover, Bt apparently does not have to be an obligate microbe in its association with insects, as it grows in regular media in vitro [ 12 ]. Nevertheless, the chemical properties of the assessed soils, which are widely known to interphere in Bt ’s survival [ 18 , 20 , 21 , 22 , 23 ], have not been analyzed.…”
Section: Niches Occupied By Btmentioning
confidence: 99%